The Fragmentation of Work, Entertainment, E-Mail, and News on a Personal Computer: Motivational Predictors of Switching Between Media Content. Issue 3 (3rd July 2018) - Yeykelis, Leo; Cummings, James J.; Reeves, Byron
ABSTRACT: Personal computers allow multitasking among a greater variety of content than has ever been possible on a single device. We logged all switches made for 4 days for 30 people on personal computers used in natural environments. The median time before a switch occurred was 11 sec, shorter than previously observed. We also measured individual differences in appetitive versus defensive motivations to switch. Those people high on both motivations ( Coactives ) had the most switches per session. Risk takers had the shortest content segment lengths; risk avoiders and inactives were lower on the number of switches and anticipated arousal. Different patterns of content selection, in addition to switching behavior, were also observed for the different motivation activation groups. Results highlight how threads of experience that mix radically different short media segments may better define how people now search, process, and evaluate information. Implications in light of technological trends and individual differences are discussed.